2021
DOI: 10.1007/s40801-021-00259-2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Factor VIII Fc Fusion Protein (rFVIIIFc) in Real Life: One-Year Clinical and Economic Outcomes

Abstract: Background Recombinant factor VIII Fc fusion protein (rFVIIIFc) is the first extended half-life (EHL) recombinant clotting factor with marketing authorization; it has been available in France since October 2016. However, data and literature about rFVIIIFc in clinical practice are scarce. Objective We propose a 1-year clinical and economic outcome evaluation in patients with hemophilia A taking into consideration treatment adherence. Patients and methods We reviewed the diaries of all patients treated with rFVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 46 publications
0
28
0
3
Order By: Relevance
“…In literature, there were large disparities in the impact on the rate of haemorrhagic episodes treated, ranging from an absent or minute difference 22–25 to decreases of up to two ABR points 8,9,20 . In France, Giraud et al described a 4.4 point drop of the median ABR 14 . Our study found a minimal decline of 0.7 points of the mean ABR for our entire cohort (all FVIII products combined); the decline appeared to be mainly due to the patients treated only with rFVIII‐Fc, who presented a meaningful decrease of 2.4 points between T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, there were large disparities in the impact on the rate of haemorrhagic episodes treated, ranging from an absent or minute difference 22–25 to decreases of up to two ABR points 8,9,20 . In France, Giraud et al described a 4.4 point drop of the median ABR 14 . Our study found a minimal decline of 0.7 points of the mean ABR for our entire cohort (all FVIII products combined); the decline appeared to be mainly due to the patients treated only with rFVIII‐Fc, who presented a meaningful decrease of 2.4 points between T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
“…A 20%–30% decrease in FVIII consumption has also been observed in most cases in patients switched to rFVIII‐Fc 11–13 . Inversely, many medical teams failed to report a significant decrease in FVIII consumption post‐switch 10,14,15 …”
Section: Introductionmentioning
confidence: 99%
“…A large number of retrospective real-world studies have confirmed the efficacy of efmoroctocog alfa in the prophylaxis of bleeding observed in phase III clinical trials. The following discussion, however, only focuses on those involving > 30 PTPs from one or more European countries [31,[36][37][38][39][40][41][42][43][44][47][48][49] or the USA [50][51][52].…”
Section: Real-world Experiencementioning
confidence: 99%
“…Across the studies, changes in mean or median ABRs or bleed rates ranged from zero (i.e. no change) up to reductions of four (p ≤ 0.003 vs previous prophylaxis [40,41,47,49]); these were accompanied by reductions in the median number of weekly or yearly injections ranging from 22 to 33% (p < 0.001 vs previous prophylaxis [40,41,44,48,50]) and reductions in weekly, monthly or yearly FVIII consumption typically ranging from 10 to 40% (p ≤ 0.028 vs previous prophylaxis [31,40,44,49,50]) (Table 4).…”
Section: Real-world Experiencementioning
confidence: 99%
See 1 more Smart Citation